2020
DOI: 10.1007/s11883-020-00861-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Statins in Current Guidelines

Abstract: Purpose of Review The causal association of LDL-cholesterol (LDL-C) with atherosclerotic cardiovascular disease (ASCVD) has been demonstrated in robust experimental, epidemiological, genetic, and interventional randomized controlled trials (RCTs). The goal of this review is to show how the knowledge acquired from statin RCTs influenced and was recommended on guidelines for prevention of ASCVD during the last three decades. Recent Findings Guideline recommendations have evolved with accruing information derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…It has been proved that a high level of LDL-C is a key risk factor for ASCVD [ 42 ]. Many clinical guidelines have shown that statins lower the incidence of ASCVD by reducing the levels of LDL-C, lipid content of plaques, and FCT [ 43 , 44 ]. Patients with low level of LDL-C who were treated with statins had a higher prevalence of calcification, which means that statins may help to prevent plaque rupture by calcification [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that a high level of LDL-C is a key risk factor for ASCVD [ 42 ]. Many clinical guidelines have shown that statins lower the incidence of ASCVD by reducing the levels of LDL-C, lipid content of plaques, and FCT [ 43 , 44 ]. Patients with low level of LDL-C who were treated with statins had a higher prevalence of calcification, which means that statins may help to prevent plaque rupture by calcification [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Newer statins, including atorvastatin and rosuvastatin, have increased potency for lowering LDL-C and may achieve the desired LDL-C reduction more safely [ 106 ]. Statins remain an important component of atherosclerotic cardiovascular disease prevention and remain among the top-selling class of drugs worldwide [ 107 , 108 ].…”
Section: Current Lipid-lowering Treatments For Atherosclerosis: Succe...mentioning
confidence: 99%
“…This competition reduces the rate at which mevalonate is produced, thus inhibiting production of cholesterol in the liver [ 111 ]. In addition, statins also affect systemic cholesterol availability by promoting a compensatory decrease in circulating LDL and cholesterol transport through a variety of mechanisms [ 93 , 112 , 113 ]. The broad use of statins as first-line therapeutics for prevention of cardiovascular disease by inhibition of cholesterol synthesis raised the possibility of their effect on PCa.…”
Section: Effect Of a Class Of Drugs That Inhibit Cholesterol Synthesis On Prostate Cancer (Pca)mentioning
confidence: 99%